Fundamental equilibrium exchange rate: a case study of the Finnish Markka - Liselotte Hoej (Bank of Finland, 1995)
The purpose of this paper is to estimate the Fundamental Equilibrium Exchange Rate (FEER) for the Finnish economy and to derive a relationship between the current account and the real exchange rate in the macroeconomic equilibrium.FEER is defined as the real exchange rate which delivers a sustainable current account balance when the economy is growing at its equilibrium (non-inflationary) rate.The results emphasize the effects of the collapse of the Finnish-Soviet trade in 1991 on both the equilibrium rate of output and the equilibrium exchange rate.The assessment of the exchange rate situation prevailing in late 1994 points to the conclusion that there may be emerging conflicts in Finland between the targets of external and internal balance, unless structural reforms or the recovery of the international economy move the fundamentals from their present position.
URN:NBN:fi:bof-20140807328
Keywords: 330